A case of pediatric serum sickness like reaction (SSLR) after a 2-month re-exposure to amoxicillin - Devyani Bakshi; Xinxin Tang; Susan Waserman (Allergy, Asthma & Clinical Immunology, 2024)
Abstract Background Serum-sickness like reactions (SSLRs) to amoxicillin have been documented in the medical literature. Beta-lactams are important and commonly used medications especially in the pediatric population. Often, SSLRs present within days of and during first exposure/ingestion to the offending agent. We described a unique case of a 4-year-old boy who presented with symptoms of amoxicillin SSLR following his second course of amoxicillin with only 2 months and 10 days between his second and first course. Case presentation A 4-year-old boy presented to hospital with a pruritic rash on day 7 of a 10-day course of amoxicillin for otitis media accompanied by fever (38.7 degrees Celsius). On day 7 of his second course of amoxicillin, which was separated from his first course by only 2 months and 10 days, his mother noticed erythematous, raised, pruritic lesions with central clearing on his sternum. He presented to the ED with emesis, progression of the rash to his torso, back, legs, and face, hypotension, angioedema, and joint pain. His bloodwork demonstrated a leukocytosis of 18.6 × 109 g/L with neutrophilic predominance and thrombocytosis with a platelet count of 653 × 109 g/L. He was treated with 5 mg oral cetirizine daily and 1 mg/kg oral prednisone which improved his rash and angioedema. He was managed with up to 4 times the usual dose of cetirizine. He was assessed in our outpatient clinic as an outpatient and penicillin skin testing was unremarkable. A diagnosis of a probable SSLR to amoxicillin was made. Conclusion We report an unusual presentation of SSLR following re-exposure to amoxicillin. Our case highlights that patients with previous asymptomatic exposure to amoxicillin can develop SSLR with repeat exposure. Although it is not uncommon for children to develop amoxicillin SSLRs after previous exposure to the drug, this case is unique because of its short time course of 2 months and 10 days months between drug courses. Penicillins are commonly used in the pediatric population. Therefore, it is important to correctly characterize adverse drug reactions to broaden our understanding of SSLRs, prevent unnecessary avoidance of the triggering agent, and improve patient management.